Ageing in corrective services: from the perspective of prison chaplains. Issue 1 (2nd January 2019) - Shaw, R.; Stevens, B.; Paget, J.; Snoyman, P.
Abstract : The number of older inmates in New South Wales prisons has increased over the past ten years but it is unclear whether corrective services can cater for the increase. The current study reports the results of a qualitative study about ageing in prison. Eight prison chaplains from four corrective facilities in NSW were interviewed using a semi-structured interview schedule. The results of a thematic analysis revealed four main themes: the system, the services, the environment and the inmate . The themes reveal a system that is not designed to cope with an ageing population. Inmates become resentful of what has happened to them rather than for the damage they have done to somebody else. The system lacks processes and programmes to enable proper rehabilitation. The issues raised by the chaplains in terms of services, the environment and the inmates decrease the possibility that an older inmate will adapt to the environment and successfully age in place.